The reversal of populism. assessing the explanatory power of the ideational approach in contemporary Argentina - Sendra, Mariana and Llamazares, Iván (International Political Science Review)
In this study we conduct a least-likely case study in order to assess the analytical power of the ideational approach to populism. We do so by testing the direct and conditional effects of populist attitudes on vote choices in Argentina. We examine whether populist attitudes are associated with the Peronist vote, as more essentialist interpretations would lead us to expect, or, on the contrary, linked to vote for right parties, an expectation that is more consistent with thin-ideological approaches. Our data consists of an original online survey carried out in September 2020, a specific juncture at which the Peronist government had to deal with widespread popular discontent caused by intense economic crisis and the COVID-19 pandemic. Our findings reveal that populist attitudes are positively associated with voting for right parties and that the effects of such attitudes are conditioned by ideological preferences. These results underscore the explanatory power of ideational approaches to the electoral activation of populist attitudes.- Reproduced
Keywords: Populist attitudes, Ideational theory, Vote choices, Center-right parties, Argentina